INDEKS AL-QUR’AN DI INDONESIA: (Studi Komparatif Buku-Buku Indeks Al-Qur’an di Indonesia 1984-2007) - Ahmad Syarif Hidayatullah (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
This study aims to determine the method and technical writing of some Quran index books in Indonesia written in the period 1984-2007. This research was conducted by library research with historical approach. This study give some information that the books of Quran Index written in the period 1984-2007 by Indonesian Muslim scholars were all written using alphabetic form and their writing presented in global and detailed form. Books of Quran index by Indonesian scholars which were written individually or collectively are not separated from the influences of Quran index books created by non Indonesian scholars. These facts are indicated by some references used in the preparation of their works. Among the